Recombinant Factor VIIa rFVIIa : current and future indications - Scharrer, Inge; Depka Prondzinski, Mario von (Weller Verlag, 2000)
A collection of papers presented at a workshop that focused on the role of recombinant factor VIIa in treatment of coagulation protein disorders. Intended for professional public.
Keywords: Factor VIIa; klinické lékařství; Recombinant Proteins; rekombinantní proteiny; hematologie a transfuzní lékařství; Clinical Medicine; poruchy koagulačních proteinů; Coagulation Protein Disorders; faktor VIIa; hematologie; Education; koagulancia; výchova a vzdělávání; Hematology; genetika, lékařská genetika; Coagulants